2007
DOI: 10.2486/indhealth.45.328
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Work Duration or Physical Symptoms on Mental Health among Japanese Visual Display Terminal Users

Abstract: The present study examined the relationship of work duration or physical symptoms to the mental health of visual display terminal (VDT) workers in Japan. The mental health status of 2,327 VDT users at an administrative office was investigated using the 12-item General Health Questionnaire (GHQ-12). Subjects were asked about their age, sex, hours of daily VDT use, rest and breaks during VDT work, eyestrain, and musculoskeletal pain. Logistic regression analysis was used to evaluate the associations with mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
1
28
2
Order By: Relevance
“…CVS was measured using questionnaires, which did not follow a standard pattern, and the prevalence results were highly disparate: under 20% in the study of Ye et al [17] and over 80% in that of T amez-Gonz alez et al [21]. CVS was quantified only in the study of Carta et al [19] who, after evaluating the occurrence of 12 symptoms, calculated a score using a mathematical expression based on the frequency and intensity of the perceived symptoms and also on the specificity of the symptoms; they gave higher scores to those symptoms that (in a prior calculation) had a significant association with computer exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CVS was measured using questionnaires, which did not follow a standard pattern, and the prevalence results were highly disparate: under 20% in the study of Ye et al [17] and over 80% in that of T amez-Gonz alez et al [21]. CVS was quantified only in the study of Carta et al [19] who, after evaluating the occurrence of 12 symptoms, calculated a score using a mathematical expression based on the frequency and intensity of the perceived symptoms and also on the specificity of the symptoms; they gave higher scores to those symptoms that (in a prior calculation) had a significant association with computer exposure.…”
Section: Discussionmentioning
confidence: 99%
“…There are even differences about the criteria used to establish when the worker is considered symptomatic, given the lack of validated measurement instruments. The instruments used for diagnosis are usually unstructured questionnaires focusing on the frequency of occurrence of the symptoms [14e16], their intensity [17], or both [18,19], for example, in the studies of Carta et al [19] and Fenga et al [20]. The first study asks about the frequency (number of episodes per week) and intensity (on a scale of 1 to 5) of 12 symptoms (burning, eye pain, headache, eye redness, photophobia, tearing, repeated blinking, heavy eyelids, itching, blurred vision at distance and near, and double vision); workers are then classified as asymptomatic or with insignificant, mild, or intense symptomatology according to the score obtained on the questionnaire, yielding a CVS prevalence of around 50%.…”
Section: What Is New?mentioning
confidence: 99%
“…[56] reported that the likelihood of developing physical symptoms such as headache, neck pain, back pain, and eye strain increased when daily exposure to VDTs exceeded 3 h, and that mental and sleep disorders could be prevented by restricting the use of VDTs to ≤ 5 h/day. In addition, prolonged and uninterrupted daily VDT usage causes eye strain and musculoskeletal pain, both of which are associated with deterioration of mental health [57, 58]. Because TMD is considered a symptom of the musculoskeletal system, it is conceivable that VDT use has an indirect influence on TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Given the improvement in the quality of electronic monitors, one might conjecture that the prevalence of computer‐related visual symptoms should have declined over time. However, more recent investigations have also noted a very wide range of prevalence rates ranging from 19.6% 3 to 72% 4 . In each of these latter studies, prevalence rates refer specifically to the symptom of eyestrain or asthenopia.…”
mentioning
confidence: 99%